Polyimide-derived graphene coated catalyst as well as preparation method and application thereof
By using polyimide-derived graphene-encapsulated platinum catalyst, the problem of inactivation of precious metal catalysts in an acidic environment is solved, and the catalytic effect of high activity, high selectivity and long life is achieved, and the yield of para-aminophenol is improved.
Patent Information
- Application Number
- CN202411861261.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-17
AI Technical Summary
In the prior art, when using precious metal-supported catalysts in sulfuric acid environments, they are prone to inactivate due to corrosion, and the yield of PAP is low, making it difficult to meet industrial needs.
A platinum catalyst is encapsulated with polyimide (PI) derived graphene derived from platinum catalyst, which forms a carbon coating with high activity and stability by controlling the carbon source precursor, the carbonization temperature, the treatment atmosphere and the carbonization time, protecting the platinum catalyst from acid corrosion.
It achieves the high activity and selectivity of the catalyst in an acidic environment, extends the life of the catalyst, improves the yield of PAP, and solves the problem of inactivation of traditional catalysts in an acidic environment.
Smart Images

Figure BDA0005193258950000101 
Figure HDA0005193258970000011 
Figure HDA0005193258970000012
Abstract
Description
(I) Technical field
[0001] The invention relates to a polyimide (PI)-derived graphene-wrapped platinum-based catalyst, a preparation method thereof, and application of the catalyst in preparing p-aminophenol by hydrogenation and rearrangement of nitrobenzene. (II) Background technology
[0002] Para-aminophenol (PAP) is an important chemical raw material and organic intermediate, widely used in the synthesis of important chemicals such as medicine, rubber, dyes, pesticides, antioxidants and photosensitive materials. Especially in the pharmaceutical industry, PAP is the raw material for the synthesis of antipyretic and analgesic drugs such as acetaminophenol, as well as drugs such as adipine, antoconazole, vitamin B, and complex amides. In addition, in the rubber industry, PAP can be used to synthesize paraphenylenediamine antioxidants with the characteristics of high efficiency, non-toxicity, and pollution-free. They are supporting antioxidants for radial tire products. In the dye industry, it can be used as an intermediate for a variety of dyes, used in the synthesis of dispersed materials, sulfur dyes, acid dyes, azo dyes and fur dyes. Para-aminophenol is also used in the synthesis of herbicides and pesticides, as well as antioxidants, petroleum product additives, acrylonitrile dimerization catalysts, inhibitors of urea addition reactions, and the production of photographic developers.
[0003] The synthesis process of PAP can be mainly divided into the p-nitrophenol method, p-nitrochlorobenzene method, phenol method, nitrobenzene (NB) method, etc. according to the raw material route. The nitrobenzene method for preparing PAP usually uses precious metal-supported materials as hydrogenation catalysts and liquid sulfuric acid as rearrangement catalysts. The reaction process is as follows: First, nitrobenzene is hydrogenated at the metal active site to generate the intermediate product phenylhydroxylamine (PHA), and then PHA undergoes a Bamberger rearrangement reaction under the action of an acidic catalyst to generate PAP. Since sulfuric acid is highly corrosive, conventional supported metal catalysts are easily corroded and lost, causing catalyst deactivation. Conventional solid acids are used instead of sulfuric acid. Although the corrosion problem can be solved, the yield of PAP is very low. Therefore, it is particularly important to design and synthesize a new catalyst with excellent hydrogenation selectivity and resistance to strong acid corrosion.
[0004] Graphene-coated catalysts have attracted much attention due to their high activity and good stability. The structure of the carbon coating has a significant effect on the catalytic performance. Chinese patent CN201711330761.3 discloses a carbon-coated nano-iron-based Fischer-Tropsch synthesis catalyst and a preparation method thereof. A hydroxyl-rich carbon-containing compound is used as a carbon source, and a co-impregnation-in-situ carbonization strategy is adopted to prepare a carbon-coated nano-iron-based Fischer-Tropsch synthesis catalyst, which improves the Fischer-Tropsch reaction performance. Chinese patent CN116726937A discloses a method for preparing a transition bimetallic catalyst wrapped in a graphene-like carbon shell. The catalyst can efficiently convert cellulose into hydroxyacetone, and the catalyst exhibits excellent activity during the reaction. However, there are currently no reports on the application of polyimide-derived carbon-coated precious metal catalysts in acidic environments.
[0005] Polyimide (PI) is a polymer material containing an imide ring structure in the main chain. As a nitrogen-rich polymer, it has become a hot topic in the research of new functional carbon materials. Unlike many easily dissociated polymers, its high thermal stability and controllable morphology are conducive to the formation of carbon materials with unique morphology.
[0006] The present invention studies the influence of the synthesis process based on different raw materials on the PI structure, and also studies the influence of the obtained PI with different structures on the performance of graphene-coated catalysts, providing new ideas and methods for expanding the application scope of carbon-coated catalysts. (III) Summary of the invention
[0007] The present invention aims to provide a polyimide (PI)-derived graphene-wrapped platinum catalyst, a preparation method thereof, and application of the catalyst in the preparation of p-aminophenol by hydrogenation of nitrobenzene.
[0008] In order to solve the above-mentioned invention object, the present invention adopts the following technical scheme
[0009] In a first aspect, the present invention provides a method for preparing a polyimide (PI)-derived graphene-wrapped platinum catalyst, the preparation method comprising:
[0010] (1) dissolving a diamine in an organic solvent, adding a dianhydride after the diamine is completely dissolved in the solvent, and continuously stirring the reaction at room temperature for 2 to 8 hours to obtain a polyamic acid (PAA) solution; weighing a supported platinum catalyst, wherein the supported platinum catalyst includes a carrier and a metal active component supported on the carrier, wherein the metal active component is platinum, adding the supported platinum catalyst to the polyamic acid solution, stirring for 0.5 to 5 hours, then ultrasonicating for 10 to 30 minutes, and continuing to stir overnight to obtain a mixture;
[0011] (2) Then, the mixture obtained in step (1) is transferred to a polytetrafluoroethylene-lined autoclave and heated in an oven at 150 to 200° C. for 8 to 15 hours. The obtained mixture is cooled to room temperature, washed, filtered, and vacuum dried to obtain a dry product;
[0012] (3) The dried product obtained in step (2) is ground and calcined in a nitrogen atmosphere at 200-400° C. for 2-5 hours, and then calcined at 500-900° C. for 2-112 hours in an inert protective atmosphere, a hydrogen atmosphere or a vacuum state to obtain a polyimide-derived graphene-encapsulated platinum catalyst.
[0013] Furthermore, in step (1), the diamine is selected from one or more of ethylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, and p-phenylenediamine.
[0014] Furthermore, the organic solvent for dissolving the diamine in step (1) can be one or more of acetonitrile, dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), and N-methylpyrrolidone (NMP).
[0015] Furthermore, in step (1), the dianhydride is selected from one or more of pyromellitic dianhydride, 4,4'-biphenyl ether dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, and 3,3',4,4'-benzophenone tetracarboxylic dianhydride.
[0016] Furthermore, in step (1), the molar ratio of dianhydride to diamine is 1:(0.3-1.3).
[0017] Furthermore, the carrier of the supported platinum catalyst in step (1) is activated carbon, TiO 2 Or diatomaceous earth.
[0018] Furthermore, the loading amount of platinum in the supported platinum catalyst in step (1) (relative to the carrier) is 0.5 to 5 wt %.
[0019] Furthermore, in the step (1), the mass ratio of the supported platinum catalyst to the dianhydride is 1:(0.25-4).
[0020] Furthermore, in the step (2), the washing reagents are DMAC and ethanol, and the number of washing times can be selected according to needs, preferably multiple washings are performed to remove unnecessary impurities.
[0021] Furthermore, in the step (2), the vacuum drying temperature is 20 to 80° C., and the vacuum drying time is 2 to 30 hours.
[0022] Furthermore, the inert protective atmosphere in step (3) is at least one of nitrogen, argon and helium.
[0023] In the present invention, the supported platinum catalyst can be a commercially available product or can be prepared by itself according to methods reported in literature.
[0024] In a second aspect, the present invention provides a polyimide (PI)-derived graphene-wrapped platinum catalyst prepared according to the preparation method described in the first aspect.
[0025] In a third aspect, the present invention provides the use of the polyimide (PI)-derived graphene-wrapped platinum catalyst described in the second aspect in the preparation of p-aminophenol by hydrogenation and rearrangement of nitrobenzene.
[0026] Furthermore, the specific method of the application is: adding distilled water, 98wt% concentrated sulfuric acid, nitrobenzene, a surfactant, and a polyimide-derived graphene-wrapped platinum catalyst into an intermittent hydrogenation reactor, with the mass ratios of 100-300: 10-50: 20-200: 0.2-0.6: 0.5-2, respectively, introducing hydrogen and carrying out a hydrogenation rearrangement reaction under stirring conditions to obtain the target product p-aminophenol.
[0027] Furthermore, the surfactant is hexadecyltrimethylammonium chloride.
[0028] Furthermore, the reaction temperature of the hydrogenation rearrangement reaction is 50-150° C., and the hydrogen pressure in the reactor is 0.6-2.0 MPa.
[0029] The present invention provides a method for preparing a polyimide-derived carbon-wrapped platinum catalyst and its application in preparing p-aminophenol by hydrogenation of nitrobenzene. By controlling the carbon source precursor, carbonization temperature, treatment atmosphere and carbonization time, a carbon layer with different nitrogen content and configuration derived from polyimide can be obtained, and based on the electronic conductivity and quantum tunneling effect of metal and graphene materials, a catalyst with high activity, high selectivity and high stability under acidic conditions can be obtained.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] 1) The catalyst prepared by the present invention is a carbon-coated catalyst. Since the platinum catalyst is covered by a carbon layer, the metal platinum will not be lost in an acidic environment, thereby improving the acid resistance of the catalyst and its application stability is far superior to that of traditional supported catalysts.
[0032] 2) The catalyst prepared by the present invention has a carbon source of polyimide (PI), which has abundant hexagonal carbon in the imide structure and has excellent electron transport performance, providing more active sites for the reaction, thereby enhancing the catalytic activity and selectivity.
[0033] 3) In the process of preparing the catalyst, the present invention adopts a solvent thermal method to synthesize polyimide, and controls the solvent, monomer, and polymerization reaction conditions (such as temperature and time) to adjust and improve the morphology, composition, and crystallinity of the catalyst. The particle size and morphology of the coated catalyst prepared by polyimide-derived graphene can be controlled.
[0034] 4) In the present invention, PI is not easy to dissociate, and its high thermal stability and controllable morphology are conducive to the formation of carbon materials with unique morphology. The carbon-encapsulated Pt catalyst prepared by pyrolysis of a polymer with a specific structure has a small size and uniform distribution of metal PtNPs.
[0035] 5) In the catalyst prepared by the present invention, PI itself is a nitrogen-rich polymer. The introduction of heteroatom nitrogen can optimize the reaction performance of the carbon material. Without the need to introduce additional heteroatoms, the carbon material can produce intrinsic topological defects and provide additional reaction sites. In addition, the hydrogenation performance of the catalyst can be controlled by regulating the carbon layer structure, thereby improving the selectivity of the target product.
[0036] 6) The catalyst prepared by the present invention does not contain other metal elements except the metal platinum active component, and does not increase the difficulty of recycling the precious metal catalyst. (IV) Description of the drawings
[0037] Figure 1 This is a SEM image of the PI-derived graphene-wrapped platinum catalyst Pt / C@PIC prepared in Example 2. From the image, it can be clearly seen that a layer of PI structure is successfully coated on the surface of the catalyst.
[0038] Figure 2 This is a TEM image of the PI-derived graphene-wrapped platinum catalyst Pt / C@PIC prepared in Example 2. Figure (a) is a cubic graph of the catalyst particle size distribution, and Figure (b) shows that the metal Pt is directly observed to be coated by the PI-derived carbon layer.
[0039] Figure 3 This is the XRD pattern of the PI-derived graphene-wrapped platinum catalyst Pt / C@PIC prepared in Example 2. It can be seen from the figure that the catalyst shows two obvious characteristic peaks at 24.9° and 43.5°, which are respectively attributed to the (002) and (100) crystal planes of carbon. This shows that the PI-coated Pt sample can be transformed into a hexagonal structure of carbon material after high-temperature calcination, and no obvious Pt metal diffraction peak is detected, indicating that the prepared catalyst Pt metal particles have a high degree of dispersion.
[0040] Figure 4The Raman graphs of the Pt / C catalyst and the PI-derived graphene-wrapped platinum catalyst Pt / C@PIC prepared in Example 2. There are two obvious characteristic peaks in both graphs, corresponding to the D band and the G band of the carbon material, indicating that the prepared wrapped platinum catalyst shows a higher degree of graphitization.
[0041] Figure 5 This is the XPS spectrum of the PI-derived graphene-wrapped platinum catalyst Pt / C@PIC prepared in Example 2. Figure (a) is the C1s spectrum, Figure (b) is the Pt 4f spectrum, and Figure (c) is the N1s spectrum. In the figure, both carbon and nitrogen are shifted toward the low binding energy direction, indicating that under the quantum tunneling effect, the electrons of the Pt metal are transferred to the surface carbon layer, making the surface carbon layer in an electron-rich state. (V) Specific implementation methods
[0042] The technical solution of the present invention will be clearly and completely described below with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0043] Embodiment 1
[0044] Weigh 0.20g of 4,4'-diaminodiphenyl ether and dissolve it in 50mL DMAC, add 0.26g of pyromellitic dianhydride to react, stir continuously at room temperature for 4 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 2 hours, ultrasonicate for 15 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated in an oven at 150°C for 10 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, filter to remove DMAC, and vacuum dry at 60°C for 10 hours to remove moisture. Then, calcine at 200°C for 5 hours under a nitrogen atmosphere, and then raise the temperature to 700°C for high-temperature calcination for 5 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0045] Embodiment 2
[0046] Weigh 1.80g of 4,4'-diaminodiphenyl ether and dissolve it in 50mL DMF, add 2.20g of 4,4'-biphenyl ether dianhydride to react, stir continuously at room temperature for 6 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 2.5 hours, ultrasonicate for 10 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated at 150°C in an oven for 8 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, remove DMAC by suction, and vacuum dry at 30°C for 20 hours to remove moisture. Then, calcine at 200°C for 3 hours under a nitrogen atmosphere, and then raise the temperature to 650°C for high-temperature calcination for 8 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0047] Embodiment 3
[0048] Weigh 0.45g of p-phenylenediamine and dissolve it in 20mL of NMP, add 0.5g of 3,3',4,4'-biphenyltetracarboxylic anhydride to react, stir continuously at room temperature for 3 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 3 hours, ultrasonicate for 20 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated at 200°C in an oven for 11 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, filter to remove DMAC, and vacuum dry at 80°C for 14h to remove moisture. Then, calcine at 250°C for 4 hours under a nitrogen atmosphere, and then raise the temperature to 500°C for 3 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0049] Embodiment 4
[0050] Weigh 0.90g of p-phenylenediamine and dissolve it in 20mL DMAC, add 1g of 4,4'-biphenyl ether dianhydride to react, stir continuously at room temperature for 4 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 5 hours, ultrasonicate for 15 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated at 180°C in an oven for 13 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, remove DMAC by suction, and vacuum dry at 20°C for 30 hours to remove moisture. Then, calcine at 250°C for 2 hours under a nitrogen atmosphere, and then raise the temperature to 800°C for 7 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0051] Embodiment 5
[0052] Weigh 3.0g of 4,4'-diaminodiphenyl ether and dissolve it in 60mL NMP, add 3.90g of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride to react, stir continuously at room temperature for 5 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 30 minutes, ultrasonicate for 30 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated at 180°C in an oven for 9 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, filter to remove DMAC, and vacuum dry at 50°C for 2h to remove moisture. Then, calcine at 300°C for 3 hours under a nitrogen atmosphere, and then raise the temperature to 550°C for high-temperature calcination for 2 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0053] Embodiment 6
[0054] Weigh 0.45g of 4,4'-diaminodiphenyl ether and dissolve it in 60mL DMAC, add 0.59g of 3,3',4,4'-biphenyltetracarboxylic dianhydride to react, stir continuously at room temperature for 2 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 1 hour, ultrasonicate for 5 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated in an oven at 200°C for 15 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, remove DMAC by suction, and vacuum dry at 40°C for 24 hours to remove moisture. Then, calcine at 300°C for 5 hours under a nitrogen atmosphere, and then raise the temperature to 600°C for high-temperature calcination for 6 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0055] Embodiment 7
[0056] Weigh 0.1g of 4,4'-diaminodiphenyl ether and dissolve it in 40mL DMAC, add 0.12g of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride to react, stir continuously at room temperature for 7 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 4 hours, ultrasonicate for 25 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated in an oven at 170°C for 10 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, remove DMAC by suction, and vacuum dry at 70°C for 8h to remove moisture. Then, calcine at 350°C for 5 hours under a nitrogen atmosphere, and then raise the temperature to 750°C for high-temperature calcination for 10 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0057] Embodiment 8
[0058] Weigh 0.9g of 4,4'-diaminodiphenyl ether and dissolve it in 40mL DMF, add 1.2g of pyromellitic dianhydride to react, stir continuously at room temperature for 6 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 1.5 hours, ultrasonicate for 10 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated in an oven at 170°C for 14 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, filter to remove DMAC, and vacuum dry at 30°C for 18h to remove moisture. Then, calcine at 350°C for 2 hours under a nitrogen atmosphere, and then raise the temperature to 900°C for 4 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0059] Embodiment 9
[0060] Weigh 0.2g of p-phenylenediamine and dissolve it in 30mL NMP, add 0.25g of pyromellitic dianhydride to react, stir continuously at room temperature for 8 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 3 hours, ultrasonicate for 15 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated in an oven at 190°C for 12 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, remove DMAC by suction, and vacuum dry at 60°C for 26h to remove moisture. Then, calcine at 400°C for 4 hours under a nitrogen atmosphere, and then raise the temperature to 650°C for high-temperature calcination for 9 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0061] Embodiment 10
[0062] Weigh 1.8g of 4,4'-diaminodiphenyl ether and dissolve it in 30mL DMF, add 2.4g of pyromellitic dianhydride to react, stir continuously at room temperature for 4 hours, take 1g of commercially available 3wt% Pt / C, add it to the mixed solution, stir for 3.5 hours, ultrasonicate for 20 minutes, and continue stirring overnight. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and heated at 190°C in an oven for 8 hours. Cool to room temperature, wash with DMAC and ethanol several times to remove unnecessary substances, filter to remove DMAC, and vacuum dry at 80°C for 6 hours to remove moisture. Then, calcine at 400°C for 3 hours under a nitrogen atmosphere, and then raise the temperature to 850°C for high-temperature calcination for 11 hours to obtain a PI-derived graphene-wrapped platinum catalyst.
[0063] Comparative Example 1
[0064] Weigh 1.0g of commercial 3wt% Pt / C, add it into 10mL of water and mix evenly, first add 5g of 5wt% hydrogen peroxide, stir at 50℃ for 0.5h, add 3.0g of 40wt% sucrose aqueous solution, soak at room temperature for 2h, and then vacuum dry at 50℃ for 10h to remove moisture; then calcine it at 850℃ under nitrogen for 2h to obtain a sucrose-derived carbon-encapsulated platinum catalyst.
[0065] Comparative Example 2
[0066] Weigh 1.0g of commercial 3wt% Pt / C, add it into 10mL of water and mix evenly, first add 5g of 5wt% hydrogen peroxide, stir at 50°C for 0.5h, add 3.0g of 40wt% sucrose aqueous solution and 0.5g of 20wt% urea aqueous solution, soak at room temperature for 2h, and then vacuum dry at 50°C for 10h to remove moisture; then calcine it at 850°C under nitrogen for 2h to obtain a nitrogen-doped carbon-encapsulated platinum catalyst.
[0067] Comparative Example 3
[0068] Weigh 1.0g of commercial 3wt% Pt / C, add it into 10mL of water and mix evenly, first add 5g of 5wt% hydrogen peroxide, stir at 50℃ for 0.5h, add 3.0g of 50wt% glucose aqueous solution, soak at room temperature for 2h, and then vacuum dry at 50℃ for 10h to remove moisture; then calcine it at 850℃ under nitrogen for 2h to obtain a glucose-derived carbon-encapsulated platinum catalyst.
[0069] Comparative Example 4
[0070] Weigh 1.0g of commercial 3wt% Pt / C, add it into 10mL of water and mix evenly, first add 5g of 5wt% hydrogen peroxide, stir at 50℃ for 0.5h, add 3.0g of 50wt% glucose aqueous solution and 0.3g of 25wt% dicyandiamide aqueous solution, soak at room temperature for 2h, and then vacuum dry at 50℃ for 10h to remove moisture; then calcine it at 850℃ under nitrogen for 2h to obtain a nitrogen-doped carbon-encapsulated platinum catalyst.
[0071] Comparative Example 5
[0072] Weigh 1.0g of commercial 3wt% Pt / C, add it into 10mL of water and mix evenly, first add 5g of 5wt% hydrogen peroxide, stir at 50℃ for 0.5h, add 3.0g of 50wt% aqueous solution of glucosamine and 0.3g of 25wt% aqueous solution of dicyandiamide, soak at room temperature for 2h, and vacuum dry at 50℃ for 10h to remove moisture; then calcine it at 850℃ under nitrogen for 2h to obtain a nitrogen-doped carbon-encapsulated platinum catalyst.
[0073] Embodiment 11
[0074] 180 g of distilled water, 30 g of 98 wt % concentrated sulfuric acid, 60 g of nitrobenzene, 0.3 g of hexadecyltrimethylammonium chloride, and 0.9 g of the supported carbon-encapsulated platinum catalyst prepared in Example 1 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 115 ° C, the hydrogen pressure was 0.8 MPa, stirring was started, the stirring rate was 1000 r / min, the reaction was carried out at a constant temperature, the reaction was stopped at the reaction end point, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 88.4 wt %.
[0075] Embodiment 12
[0076] 120 g of distilled water, 50 g of 98 wt % concentrated sulfuric acid, 70 g of nitrobenzene, 0.45 g of hexadecyltrimethylammonium chloride, and 0.5 g of the supported carbon-encapsulated platinum catalyst prepared in Example 2 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 80° C. and the hydrogen pressure was 2 MPa, stirring was started, the stirring rate was 900 r / min, and the reaction was carried out at a constant temperature until the reaction end point was stopped, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 87.6 wt %.
[0077] Embodiment 13
[0078] 100 g of distilled water, 15 g of 98 wt % concentrated sulfuric acid, 20 g of nitrobenzene, 0.2 g of hexadecyltrimethylammonium chloride, and 1.6 g of the supported carbon-encapsulated platinum catalyst prepared in Example 3 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 120° C. and the hydrogen pressure was 1 MPa, stirring was started, the stirring rate was 750 r / min, the reaction was carried out at a constant temperature, and the reaction was stopped at the reaction end point, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 88.2 wt %.
[0079] Embodiment 14
[0080] 240 g of distilled water, 10 g of 98 wt % concentrated sulfuric acid, 80 g of nitrobenzene, 0.4 g of hexadecyltrimethylammonium chloride, and 1.4 g of the supported carbon-encapsulated platinum catalyst prepared in Example 4 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 70° C. and the hydrogen pressure was 1.2 MPa, stirring was started, the stirring rate was 700 r / min, and the reaction was carried out at a constant temperature until the reaction end point was reached, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 86.8 wt %.
[0081] Embodiment 15
[0082] 200 g of distilled water, 35 g of 98 wt % concentrated sulfuric acid, 30 g of nitrobenzene, 0.25 g of hexadecyltrimethylammonium chloride, and 0.6 g of the supported carbon-encapsulated platinum catalyst prepared in Example 5 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 85° C. and the hydrogen pressure was 0.6 MPa, stirring was started, the stirring rate was 950 r / min, the reaction was carried out at a constant temperature, and the reaction was stopped at the reaction end point, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 87.5 wt %.
[0083] Embodiment 16
[0084] 140 g of distilled water, 20 g of 98 wt % concentrated sulfuric acid, 50 g of nitrobenzene, 0.55 g of hexadecyltrimethylammonium chloride, and 1.2 g of the supported carbon-encapsulated platinum catalyst prepared in Example VI were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 75° C. and the hydrogen pressure was 1.4 MPa, stirring was started, the stirring rate was 800 r / min, and the reaction was carried out at a constant temperature until the reaction end point was stopped, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 88.9 wt %.
[0085] Embodiment 17
[0086] 220 g of distilled water, 45 g of 98 wt % concentrated sulfuric acid, 40 g of nitrobenzene, 0.4 g of hexadecyltrimethylammonium chloride, and 0.3 g of the supported carbon-wrapped platinum catalyst prepared in Example 7 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 110° C. and the hydrogen pressure was 1.6 MPa, stirring was started, the stirring rate was 1000 r / min, and the reaction was carried out at a constant temperature until the reaction end point stopped the reaction, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 88.6 wt %.
[0087] Embodiment 18
[0088] 160 g of distilled water, 25 g of 98 wt % concentrated sulfuric acid, 30 g of nitrobenzene, 0.35 g of hexadecyltrimethylammonium chloride and 1 g of the supported carbon-encapsulated platinum catalyst prepared in Example 8 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 95° C. and the hydrogen pressure was 1 MPa, stirring was started, the stirring rate was 900 r / min, and the reaction was carried out at a constant temperature until the reaction end point was reached, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 87.1 wt %.
[0089] Embodiment 19
[0090] 300 g of distilled water, 40 g of 98 wt % concentrated sulfuric acid, 100 g of nitrobenzene, 0.6 g of hexadecyltrimethylammonium chloride, and 1.8 g of the supported carbon-encapsulated platinum catalyst prepared in Example 9 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 90° C. and the hydrogen pressure was 2 MPa, stirring was started, the stirring rate was 850 r / min, the reaction was carried out at a constant temperature, and the reaction was stopped at the reaction end point, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was diluted to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 87.6 wt %.
[0091] Embodiment 20
[0092] 260 g of distilled water, 50 g of 98 wt % concentrated sulfuric acid, 90 g of nitrobenzene, 0.5 g of hexadecyltrimethylammonium chloride and 2 g of the supported carbon-encapsulated platinum catalyst prepared in Example 10 were added to an intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 100 ° C and the hydrogen pressure was 1.8 MPa, stirring was started, the stirring rate was 800 r / min, and the reaction was carried out at a constant temperature until the reaction end point stopped the reaction, the reaction solution was taken out, the catalyst was filtered and recovered, the filtrate was fixed to a 250 mL volumetric flask, and the HPLC was used for detection. The external standard method was used for quantitative analysis, and the nitrobenzene conversion rate was 100 wt %, and the p-aminophenol selectivity was 88.7 wt %.
[0093] Embodiment 21
[0094] The application performance of the polyimide-derived graphene-coated supported metal catalyst prepared in Example 6 in the reaction of preparing p-aminophenol by hydrogenation rearrangement of nitrobenzene in Example 16 was investigated, and 5 wt% of fresh catalyst was added each time during the catalyst application process. The results are shown in Table 1, and the prepared PI-derived graphene-coated platinum catalyst still has high activity and selectivity after 10 reactions.
[0095] Table 1 Stability of polyimide-derived carbon-coated supported metal catalysts in the hydrogenation and rearrangement of nitrobenzene to prepare p-aminophenol.
[0096] Number of applications Nitrobenzene conversion rate / % Selectivity for aminophenol / % 1 100 88.9 2 100 88.6 3 100 87.6 4 100 88.5 5 100 87.6 6 100 87.4 7 100 88.6 8 100 87.5 9 100 87.6 10 100 88.8
[0097] Embodiment 22
[0098] Referring to Example 16, the carbon-coated supported metal catalysts prepared in Comparative Examples 1, 2, 3, 4 and 5 were used for the hydrogenation rearrangement of nitrobenzene to prepare p-aminophenol under the same conditions. Reaction conditions: 140g of distilled water, 20g of 98wt% concentrated sulfuric acid, 50g of nitrobenzene, 0.55g of hexadecyltrimethylammonium chloride, and 1.2g of the supported carbon-coated platinum catalyst prepared in Example 6 were added to the intermittent hydrogenation reactor, the reactor was closed, the air in the reactor was replaced with nitrogen three to five times, and then replaced with hydrogen three to five times; the temperature was raised to 75°C, the hydrogen pressure was 1.4MPa, stirring was started, the stirring rate was 800r / min, and the reaction was carried out at a constant temperature. The reaction results are shown in Table 2. Compared with Example 6, the conversion rate and selectivity were greatly reduced.
[0099] Table 2 Performance of carbon-coated supported metal catalysts prepared using different carbon sources in the hydrogenation and rearrangement of nitrobenzene to prepare p-aminophenol.
[0100]
[0101]
[0102] By comparing the above results, it can be seen that the PI-derived graphene-wrapped platinum catalyst prepared by the present invention has good activity, high selectivity and long catalyst life.
Claims
1. A method for preparing a polyimide (PI)-derived graphene-wrapped platinum catalyst, characterized in that: The preparation method is: (1) dissolving a diamine in an organic solvent, adding a dianhydride after the diamine is completely dissolved in the solvent, and continuously stirring the reaction at room temperature for 2 to 8 hours to obtain a polyamic acid solution; weighing a supported platinum catalyst, wherein the supported platinum catalyst includes a carrier and a metal active component supported on the carrier, wherein the metal active component is platinum, adding the supported platinum catalyst to the polyamic acid solution, stirring for 0.5 to 5 hours, then ultrasonicating for 10 to 30 minutes, and continuing to stir overnight to obtain a mixture; (2) transferring the mixture obtained in step (1) into a polytetrafluoroethylene-lined autoclave and heating it in an oven at 150 to 200° C. for 8 to 15 hours, cooling the obtained mixture to room temperature, washing, filtering, and vacuum drying to obtain a dry product; (3) The dried product obtained in step (2) is ground and calcined in a nitrogen atmosphere at 200-400° C. for 2-5 hours, and then calcined at 500-900° C. for 2-112 hours in an inert protective atmosphere, a hydrogen atmosphere or a vacuum state to obtain a polyimide-derived graphene-encapsulated platinum catalyst.
2. The preparation method according to claim 1, characterized in that: In the step (1), the diamine is selected from one or more of ethylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, and p-phenylenediamine; the dianhydride is selected from one or more of pyromellitic acid dianhydride, 4,4'-biphenyl ether dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride; and the molar ratio of the dianhydride to the diamine is 1:(0.3-1.3).
3. The preparation method according to claim 1, characterized in that: The carrier of the supported platinum catalyst in step (1) is activated carbon, TiO2 or diatomaceous earth.
4. The preparation method according to claim 1, characterized in that: In the step (1), the amount of platinum in the supported platinum catalyst relative to the carrier is 0.5 to 5 wt %.
5. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the supported platinum catalyst to the dianhydride is 1:(0.25-4).
6. A polyimide-derived graphene-wrapped platinum catalyst prepared according to the preparation method of any one of claims 1 to 5.
7. Use of the polyimide-derived graphene-wrapped platinum catalyst as claimed in claim 6 in the preparation of p-aminophenol by hydrogenation rearrangement of nitrobenzene.
8. The use according to claim 7, characterized in that: The specific application method is: adding distilled water, 98wt% concentrated sulfuric acid, nitrobenzene, a surfactant, and a polyimide-derived graphene-wrapped platinum catalyst into an intermittent hydrogenation reactor, wherein the mass ratios thereof are 100-300: 10-50: 20-200: 0.2-0.6: 0.5-2, respectively; introducing hydrogen gas to carry out a hydrogenation rearrangement reaction under stirring conditions to obtain the target product, p-aminophenol.
9. The use according to claim 8, characterized in that: The surfactant is hexadecyltrimethylammonium chloride.
10. The use according to claim 8, characterized in that: The reaction temperature of the hydrogenation rearrangement reaction is 50-150° C., and the hydrogen pressure in the reactor is 0.6-2.0 MPa.
Citation Information
Patent Citations
Nano-iron-based fischer-tropsch synthesis catalyst of carbon-coated structure and preparation method and application thereof
CN107999081A
Graphene-like carbon shell layer coated transition bimetallic catalyst and method for preparing hydroxyacetone through catalytic hydrogenolysis of cellulose
CN116726937A
Preparation method of efficient and stable fuel cell catalyst material
CN107069054A
Graphene metal composite material and preparation method thereof
CN109293359A
Carbon-based support polyimide array and preparation method and energy storage application thereof
CN109546137A
Cited By
Preparation method of temperature-resistant nano alkenyl gas desorption agent and application of temperature-resistant nano alkenyl gas desorption agent in coal mine drainage and mining
CN121775822A